MANAGEMENT OF RECURRENT EXFOLIATIVE CHEILITIS A/R LABIUM SUPERIOR AND INFERIOR IN PATIENT 12-YEAR-OLD - Tjokorda Istri Rismarsa Ananda Puteri; Zwista Yulia Dewi (Fakultas Kedokteran Gigi Unjani, 2022)
Exfoliative Cheilitis (EC) is a chronic inflammatory condition of the lips, characterized by fissuring, desquamation, and the formation of a bleeding crust. EC causes a burning sensation of varying intensity and sometimes bleeding. EC has no clear etiology but is associated with bad habits such as lip licking and biting, stress or depression, and systemic disease states. The best treatment for EC is to eliminate the cause or predisposing factor. Treatment was given in the form of topical corticosteroid application and petroleum jelly. The use of corticosteroids can be discontinued if there are no complaints and to overcome the dryness of the lips it is recommended to apply petroleum jelly. One week after the treatment, there was a wound healing process, but the condition of the lips still showed redness and the patient's lips were still peeling. After one month, the patient's lips have healed, and the patient's bad habits such as licking the lips and peeling the lips have disappeared. DOI : 10.54052/jhds.v2n1.p27-38